Factors associated with Mediterranean diet adherence in a sample of high socio-economic status children from southern Spain - Gracia Cristina Villodres; Federico Salvador Pérez; José Joaquín Muros (Cambridge University Press, 2024)
Abstract Objective: The present study examined the association of BMI, fat mass, physical activity engagement (PA), maximal oxygen consumption (VO2max), screen time and academic performance (AP) with Mediterranean diet (MD) adherence in a sample of high socio-economic status (SES) children. Design: A non-randomised design was used. A multilinear regression model was developed using backward elimination. Analysis included variables pertaining to age, BMI, VO2max, fat percentage, AP, PA engagement and screen time. All participants had a high SES and so this variable was not included as a predictor. Data met the assumptions required for multiple regressions in terms of linearity, homoscedasticity, normality, independence and non-multicollinearity. Setting: Two state and three mixed funding schools in Granada, Spain. Participants: Data were collected from 244 children aged between 10 and 12 years. Results: Better AP, higher PA engagement and lower screen time were found to be predictive of MD adherence. These variables explained 22·9 % of the variance in data measuring adolescent MD adherence. Conclusions: The present study suggests that, in addition to SES, PA, AP and screen time are important components to consider when targeting improvements in MD adherence in children. It is, therefore, concluded that interventions targeting improvements in PA, AP and screen time are needed to promote MD adherence in children, regardless of SES.